Antimicrobial resistance and virulence markers in methicillin sensitive Staphylococcus aureus isolates associated with nasal colonization. (April 2016) - Sarkar, Abdullah; Raji, Adeola; Garaween, Ghada; Soge, Olusegun; Rey-Ladino, Jose; Al-Kattan, Wael; Shibl, Atef; Senok, Abiola
Abstract: Most Staphylococcus aureus infections occur in previously colonized persons who also act as reservoirs for continued dissemination. This study aimed to investigate the carriage of antimicrobial resistance and virulence markers in S. aureus isolates associated with nasal colonization. The study was conducted from December 2013–April 2014. Nasal swabs were collected and questionnaires administered to 97 medical students in Riyadh Saudi Arabia. Bacterial culture, identification and antimicrobial susceptibility testing were performed by conventional methods and chromogenic agar was used for methicillin resistant S. aureus (MRSA) screening. Molecular characterization of isolates was carried out using the StaphyType DNA microarray. Thirty two students (43%) had S. aureus nasal carriage (MSSA = 31; MRSA = 1). Seventeen clonal complexes (CC) were identified namely: CC15-MSSA (n = 5), CC1-MSSA-SCC fus (n = 4), CC8-MSSA (n = 3), CC22-MSSA (n = 3), CC25-MSSA (n = 3), CC101-MSSA (n = 2). Other CC found as single isolates were CC5-MSSA, CC6-MSSA, CC30-MSSA, CC45-MSSA, CC96-MSSA, CC188-MSSA, CC398-MSSA, CC942-MSSA/ PVL +, CC1290-MSSA, ST2482-MSSA, CC80-MRSA-IV/ PVL +. The CC1-SCC fus isolates harbored the Staphylococcal cassette chromosome ( SCC ) with ccr A-1; ccr B-1 and ccr B-3 genes plus the putative fusidic acid resistance marker Q6GD50. One MSSA isolate was genotyped as coagulase negative Staphylococcus spp with an irregular composite SCC mec element. Majority of the isolates harbored various virulence genes including the hemolysin, enterotoxin, and exfoliative genes as well as various adhesive protein producing genes. Although there was low carriage of MRSA, the MSSA isolates harbored various resistance and virulence genes including those usually seen in MRSA isolates. The presence of isolates with incomplete SCC mec elements plus putative resistance and virulence genes is of concern. Highlights: Low carriage of methicillin resistant Staphylococcus aureus (MRSA) in the study population. Methicillin sensitive S. aureus colonizers habour virulence and resistance genes usually associated with MRSA isolates. Identification of coagulase negative Staphylococcus harboring irregular/ composite SCCmec element. Presence of un-typeable MSSA with the potential to evolve into novel MRSA clones.